It turned into something else: patients’ long-term experiences of transitions to or from telepsychotherapy during the COVID-19 pandemic - von Below, Camilla; Bergsten, Jenny; Midbris, Therése; Philips, Björn; Werbart, Andrzej (Frontiers in Psychology, 2023)
The shift from in-person therapy to telepsychotherapy during the COVID-19 pandemic was unprepared for, sudden, and inevitable. This study explored patients’ long-term experiences of transitions to telepsychotherapy and back to the office, applying qualitative methodology. Data were collected approximately two years after the declaration of COVID-19 as a pandemic. Eleven patients participated (nine women and two men, aged 28 to 56, six in psychodynamic psychotherapy, five in CBT). Treatments switched between in-person and video/telephone sessions. We used inductive thematic analysis. The results showed that (1) the patients experienced the process in telepsychotherapy as impeded. Interventions were difficult to understand and lost impact. Routines surrounding the therapy sessions were lost. Conversations were less serious and lost direction. Also (2), understanding was made more difficult when the nuances of non-verbal communication were lost, and (3) the emotional relationship was altered. Remote therapy was perceived as something different from regular therapy, and once back in the therapy room, the patients felt that therapy started anew. The emotional presence was experienced as weakened, but some of the patients found expressing their feelings easier in the absence of bodily co-presence. According to the patients, in-person presence contributed to their security and trust, whereas they felt that the therapists were different when working remotely, behaving in a more easygoing and familiar way, as well as more solution-focused, supportive and unprofessional, less understanding and less therapeutic. Despite this, (4) telepsychotherapy also gave the patients an opportunity to take therapy with them into their everyday lives. The results suggest that in the long run, remote psychotherapy was seen as a good enough alternative when needed. The present study indicates that format alternations have an impact on which interventions can be implemented, which can have important implications for psychotherapy training and supervision in an era when telepsychotherapy is becoming increasingly common.